2005
DOI: 10.1007/s00595-005-3040-5
|View full text |Cite
|
Sign up to set email alerts
|

Disposal of Replaced Common Hepatic Artery Coursing Within the Pancreas During Pancreatoduodenectomy: Report of a Case

Abstract: A replaced common hepatic artery (RCHA) originating from the superior mesenteric artery (SMA) is a rare anomaly. We herein report such a case in a 62-year-old man who was scheduled to undergo a pancreatoduodenectomy for lower bile duct cancer. Computed tomography (CT) showed the RCHA to run along the ventral side of the pancreas. Abdominal angiography showed an RCHA originating from the SMA, which communicated with an aberrant left hepatic artery from the left gastric artery. No gastroduodenal artery was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 5 publications
0
30
0
Order By: Relevance
“…A combination of CT and angiographic findings can help in both the diagnosis of an anomalous RHA coursing within or along the ventral side of the pancreas as well as in selecting optimal operative procedures [13]. In our cases, MRCA was the most commonly used method in detecting HA anatomy.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A combination of CT and angiographic findings can help in both the diagnosis of an anomalous RHA coursing within or along the ventral side of the pancreas as well as in selecting optimal operative procedures [13]. In our cases, MRCA was the most commonly used method in detecting HA anatomy.…”
Section: Discussionmentioning
confidence: 88%
“…RHA from SMA may course behind, within, or along the ventral side of the pancreas [13]. In particular, Michels found that half of the RHA actually coursed through the pancreatic parenchyma, whereas the other half passed posterior to the pancreas [14].…”
Section: Discussionmentioning
confidence: 99%
“…An improper vascularization may delay the restoration of liver function. Different authors recommend arterial reconstruction in case of tumor infiltration or in cases where the intraparenchymal course not ensure an R0 resection (5,10,20,21). There are many arterial reconstructive techniques for the RHA after section.…”
Section: Discussionmentioning
confidence: 99%
“…The CHA originating from the SMA is very rare, occurring in only one case in our study. Yamamoto et al [18] put forward five methods for preserving the hepatic arterial blood flow when planning a PD for patients with the RCHA coursing in, or along, the ventral side of the pancreas. PD was performed in a usual manner following a dissection of the artery from the pancreatic parenchyma in our patient, as the RCHA coursed along the ventral side of the pancreas.…”
Section: Discussionmentioning
confidence: 99%